Uma proposta pedagógica para o uso da lousa digital tendo como base a teoria sociointeracionista - De Carli, Daniel (My University, 2014)
This work had as main goal, to guide a proposal for a pedagogical use of digital whiteboard starting from a case study in an elementary school of municipal education. In methodological terms, individual interviews were conducted with four effective teachers that they work that school with students from 3rd grade of elementary school. These interviews resulted in the research corpus that was analyzed in order to know the ''as'' the pedagogical use of digital whiteboard in the classroom. The interviews were recorded, transcribed and the treatment of the corpus was conducted based on discourse textual analysis of the Moraes and Galiazzi that includes deconstruction and unitarization, categorization and finally the metatext production or interpretive text analysis. Of the categorization process, emerged categories that treat the use of digital whiteboard rooted in traditional teaching approaches, the interest by teacher, to explore the interactive features of the digital whiteboard digital; the digital whiteboard as a facilitating instrument in the content learning of study; the need to challenge the student in search of a greater involvement of this for pedagogical activities and the reconsideration of the role of the all involved in the pedagogical activities that allowed the student to work in the digital whiteboard when the teacher's role came to be supervisor of the activity. Leaving from metatext discursive analysis, we held discussions of the pedagogical use of digital whiteboard through the lens of Vygotsky's approach sociointeracionista. Together with the discussions and still through the lens of sociointeracionista approach, we guide forms of use the digital whiteboard seeking to justify its importance as an instrument of digital technology on student learning taking into account the context of digital culture. The results show that the digital whiteboard should be an instrument for collective use and the teacher needs to take a role as guide pedagogical activities seeking to question the student in achieving these. The results also indicate that the use of digital whiteboard should provide the realization of educational activities that can explore and respect the creativity, authorship of producing a particular response or resolution of a problem, allowing students to choose different roads to reach a goal common. In this sense, the use of digital whiteboard should make it possible the students develop not only intellectual ability for the content of study, but also the emotional, critical and analytical and practical intelligence. The discussions could also guide ways of using the digital whiteboard that allow associating interesting and challenging for the student with the contents of study, thus, the use of digital whiteboard can provide better experiences for all involved in the teaching-learning process.
Este trabalho teve como objetivo principal, nortear uma proposta de uso pedagógico da lousa digital partindo de um estudo de caso realizado em uma escola de ensino fundamental da rede municipal de ensino. Em termos metodológicos, foram realizadas entrevistas individuais com quatro professores do quadro efetivo daquela escola que atuam com alunos do 3º ano do Ensino Fundamental. Estas entrevistas resultaram no corpus de pesquisa que foi analisado com o intuito de conhecer o ''como'' do uso pedagógico da lousa digital em sala de aula. As entrevistas foram gravadas, transcritas e o tratamento do corpus foi realizado com base na análise textual discursiva de Moraes e Galiazzi que compreende a desconstrução e unitarização, categorização e por fim, produção do metatexto ou texto interpretativo da análise. Do processo de categorização emergiram as categorias que tratam do uso da lousa digital enraizado em abordagens tradicionais de ensino; o interesse, por parte do professor, de explorar os recursos interativos da lousa digital; a lousa digital como instrumento facilitador no aprendizado do conteúdo de estudo; a necessidade de desafiar o aluno na busca de um maior envolvimento deste para com as atividades pedagógicas e a ressignificação do papel dos envolvidos identificada nas atividades pedagógicas que possibilitaram ao aluno trabalhar na lousa digital quando o papel do professor passou a ser de orientador da atividade. Partindo do metatexto da análise textual discursiva, realizamos as discussões do uso pedagógico da lousa digital pela lente da abordagem sociointeracionista de Vygotsky. Juntamente com as discussões e ainda pela lente da abordagem sociointeracionista, norteamos formas de uso da lousa digital buscando justificar sua importância como instrumento de tecnologia digital no aprendizado do aluno levando em consideração o contexto da cultura digital. Os resultados apontam que a lousa digital deve ser um instrumento de uso coletivo sendo que o professor precisa assumir um papel de orientador das atividades pedagógicas buscando problematizar o aluno na realização destas. Os resultados também apontam que o uso da lousa digital deve proporcionar a realização de atividades pedagógicas que possam explorar e respeitar a criatividade, a autoria de produção de uma determinada resposta ou resolução de um problema, possibilitando ao aluno trilhar caminhos distintos para chegar a um objetivo comum. Nesse sentido, o uso da lousa digital deve possibilitar que o aluno desenvolva não somente a capacidade intelectual pelo conteúdo de estudo, mas também a emocional, a crítica e a inteligência analítica e prática. Pelas discussões também pudemos nortear formas de uso da lousa digital que possibilitam associar o interessante e o desafiador para o aluno com os conteúdos de estudo, dessa forma, o uso da lousa digital poderá possibilitar melhores experiências a todos os envolvidos no processo de ensino-aprendizagem.
Keywords: Tecnologia educacional; Inovações educacionais; Ensino - Meios auxiliares; Ensino auxiliado por computador; Conhecimento e aprendizagem; Educação; Digital Whiteboard; Pedagogical Proposal